Modification of active region of resonant tunnel diode - Yatsun , К.S. (Radiotekhnika, 2021)
Interest in the study of mesoscopic structures has grown significantly in recent years. This is primarily due to the development of semiconductor technology, which makes it possible to create structures with sizes of the order of units and tens of nanometers. The linear dimensions of such structures are inferior to the de Broglie wavelength of electrons, so the transport of electrons is determined mainly by their wave properties, which, in turn, leads to a number of new effects. Mesoscopic structures include the resonant tunnel diode (RTD), first proposed by Esaki and Tsu, and which is one of the first nanoelectronic devices. It consists of a semiconductor layer with a fairly narrow band gap, a quantum well (QW) layer located between two semiconductor layers (barriers) with a wider band gap. These layers, in turn, are located between the layers (spacers) of weakly doped narrow semiconductor, followed by highly doped layers of the emitter and collector. There are one or more energy levels of dimensional quantization in the QW. Under the action of bias voltage, the current passes through the RTD only if the emitter contains electrons that can tunnel. Resonant tunneling occurs at the energy level in the QW, and from there to the collector, where the spectrum of energy states is band. RTD has a very high speed of action, for example, it is known that the nonlinear properties of RTD persist up to 104 THz. The RTD is also of great power: it is the only device of nanoelectronics that can be used at room temperatures, and on the VAC of the RTD the areas of negative differential conductivity (NDC) are observed. In this article, the principle of a resonant tunneling diode is revealed, and the phenomena of tunneling in nanophysics are examined in detail. The volt-ampere characteristic (VAC) model of a two-barrier resonance tunnel diode is calculated. The paper investigates how the change of transparency coefficients and the reflection of the potential barrier of a rectangular shape affect the VAC of the RTD. This study can be the basis for further consideration of how the modification of the active region of the resonant tunnel diode affects its characteristics. In addition, the results of the research allow us to estimate qualitatively the energy required by electrons for tunneling through the structure of the RTD.